On one simple method of rational function approximation - Kravchuk , V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is shown that it is possible to apply a method proposed by V. K. Dzyadyk for the construction of rational functions that realize a near optimal approximation of entire elementary functions. The method may be termed linear in the sense that all the coefficients of the rational functions are determined from two systems of linear algebraic equations.